Brief Current Context of the Types of Electronic Commerce in Colombia (2021)
In the current context, e-commerce has improved significantly as consumers have increased online shopping in different sectors of the economy. Therefore, the term “e-commerce” is becoming increasingly well-known and relevant for conducting business transactions. In addition, the current context of the COVID-19 pandemic has contributed to the extreme growth of e-commerce, and in the long term it will be a vital part of companies to achieve a greater competitive advantage as it offers benefits to the end consumer. However, it is important to note that there will be technological and non-technological limitations that will affect its growth. Nevertheless, the advance of information and communication technologies (ICTS) will tend to correct these limitations, consolidating the generalized increase of e-commerce worldwide. Consequently, it is pertinent that students of economics, administrative and accounting sciences, engineering, among others, expand their knowledge in e-commerce and thus be at the forefront of the different issues surrounding the digital transformation in companies and the digital economy.